Rural livelihood strategies of female headed households in former Bantustans of post-apartheid South Africa: The case of Cala, Eastern Cape Province. - Chirau, Takunda John (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
Communal areas in contemporary South Africa (that is, the former Bantustans of apartheid South Africa) continue to bear and endure, albeit in new forms, socio-economic and political vulnerabilities which are negatively affecting household livelihoods. Current studies on rural livelihoods have failed to keep pace in exploring and analysing the lived experiences and ever-changing challenges faced by these rural households. This thesis provides an understanding and explanation of the livelihood activities of specifically de facto and de jure female-headed households in the former Transkei Bantustan, with a specific focus on villages in Cala. This is framed analytically by feminist theories with their emphasis on systems of patriarchy and by a rural livelihoods framework. It uses a multiplicity of research methods, including focus group discussions, in-depth interviews, life histories and survey questionnaires. The major findings of the thesis show that the female-headed households in Cala depend upon agricultural-based activities and non-agriculturally-based activities and income (including social grants) but that they exist under conditions of extreme vulnerability which are subject to fluctuation. In the end, the livelihoods of female-headed households are precarious and unstable as they live under circumstances of poverty. However, the female heads are not mere passive victims of the rural crisis in post-apartheid South Africa, as they demonstrate qualities of ingenuity and resourcefulness including through a range of coping mechanisms. At the same time, rural communities continue to be marked by patriarchal norms and practices, including systems of chieftainship, which disempower women (including female heads), though this affects de jure heads and de facto heads differently. The thesis contributes to an understanding of rural livelihoods in communal areas (or former Bantustans) of present-day South Africa by way of 'thick descriptions' of the everyday lives of female heads in Cala. Further, in examining rural livelihoods, it highlights the importance of bringing to bear on the livelihoods framework a feminist perspective in pinpointing the additional livelihood burdens carried by rural women.
Keywords: Uncatalogued